The Adverse Impacts of Exit Exams in Higher Education: A Systematic Review - Samson Worku Teshome (Lembaga Yasin AlSys, 2025)
Exit exams in higher education are widely implemented as tools for quality assurance, accountability, and the assessment of student learning outcomes. Despite their intended benefits, these assessments have been linked to various negative consequences affecting students, institutions, and educational systems. This systematic literature review critically evaluates the adverse impacts of exit exams by synthesizing peer-reviewed studies published between 1994 and 2024, following the PRISMA framework. The analysis reveals that exit exams disproportionately disadvantage marginalized student populations, contribute to increased dropout rates, and generate significant psychological stress, resulting in detrimental academic and emotional outcomes. Furthermore, these exams frequently exhibit poor alignment with curricular objectives, thereby undermining their efficacy. Thematic analysis identifies four primary adverse effects: psychological stress, inequitable access to educational opportunities, reduced graduation rates, and misalignment with educational goals. These findings highlight the urgent need for policymakers and educators to reconsider the design and administration of exit exams, emphasizing equity, fairness, and comprehensive assessment approaches. The review concludes by advocating for alternative quality assurance mechanisms that uphold accountability while minimizing harm to students.